In-utero Exposure to Maternal Stressful Life Events and Risk of Cryptorchidism: The Raine Study - Bräuner, Elvira V.; Hickey, Martha; Hansen, Åse Marie; Doherty, Dorota A.; Handelsman, David J.; Juul, Anders; Hart, Roger (Frontiers in Endocrinology, 2019)
Cryptorchidism, registered at birth or later, is the most common birth defect in males in western countries, estimated to affect around 2-3% of newborn boys, declining to around 2% at 3 months. We have previously described a potential association between stressful life events (SLEs) in pregnancy and reduced semen quality and testosterone levels in adult offspring. Both outcomes are believed to share a common etiology with cryptorchidism thus increased risk of cryptorchidism in boys exposed to prenatal SLEs may be plausible. The risk of cryptorchidism associated with prenatal SLE amongst 1273 male Generation 2 offspring was estimated using the Western Australian Pregnancy (Raine) Study. SLEs are discrete experiences that disrupt an individual’s usual activities causing a life change and readjustment, such as death of a relative or friend, divorce, illness or job loss. Mothers prospectively reported SLEs, during pregnancy at gestational weeks (GW) 18 and 34 using a standardized 10-point questionnaire. A boy was diagnosed as cryptorchid if one or both testes was non-palpable in the scrotum and not able to be manipulated into the scrotum. Twenty-four (2%) cryptorchid boys were identified. Mean (standard deviation) of SLE exposures in GW34 was 1.1 (1.2) for non-cryptorchid boys and slightly higher 1.5 (1.8) for cryptorchid boys, similar differences were observed in GW18. Adjusted odds ratio [OR] and 95% confidence intervals (CI) for risk of cryptorchidism in early (18-weeks) and late gestation (34-weeks) according to prenatal SLE exposures were: 1.06 (95% CI: 0.77-1.45) and 1.18 (95% CI: 0.84-1.67), respectively. This is the first-time report on the possible relationships between exposure to early and late pregnancy SLEs and risk of cryptorchidism in a birth cohort. Prenatal SLE exposure was not associated with a statistically significant increase in the risk of cryptorchidism in male offspring. A small case population limits the statistical power of the study and future larger studies are required to evaluate this potential association.